Environmental justice as decolonization : political contention, innovation and resistance over indigenous fishing rights in Australia, New Zealand, and the United States - Miller Cantzler, Julia, 1974- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book corrects the tendency in scholarly work to leave Indigenous peoples on the margins of discussions of environmental inequality, by situating them as central activists in struggles to achieve environmental justice. Drawing from archival and interview data, it examines and compares the historical and contemporary processes through which Indigenous fishing rights have been negotiated in the United States, Australia and New Zealand, where three unique patterns have emerged and persist. It thus reveals the agential dynamics and the structural constraints that have resulted in varying degrees of success for Indigenous communities who are struggling to define the terms of their rights to access traditionally harvested fisheries, while also gaining economic stability through commercial fishing enterprises. Presenting rich narratives of conquest and resistance, domination and resilience, and marginalization and revitalization, the author uncovers the fundamentally cultural, political and ecological dynamics of colonization and explores the key mechanisms through which Indigenous assertions of rights to natural resources can systematically transform enduring political and cultural vestiges of colonization. A study of environmental justice as a fundamental ingredient in broader processes of decolonization, Environmental Justice as Decolonization will appeal to scholars of sociology, anthropology, environmental studies, law and Indigenous studies"--
Introduction -- Colonization and fishing in Australia, New Zealand and the United States -- State-indigenous contention, decolonization and environmental justice -- Political opportunities and obstacles : the legacies of colonization -- Indigenous resources : formal structures, allies and free spaces -- Indigenous innovation and action -- The cultural dynamics of indigenous claims-making -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Environmental justice -- Australia; Environmental justice -- New Zealand; Environmental justice -- United States; Aboriginal Australians -- Government relations; Maori (New Zealand people) -- Government relations; Indians of North America -- Government relations; Aboriginal Australians -- Fishing -- Law and legislation; Maori (New Zealand people) -- Fishing -- Law and legislation; Indians of North America -- Fishing -- Law and legislation; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General